Late Pleistocene Geomorphic Evolution of Cephalonia Island, Western Greece, Inferred from Uplifted Marine Terraces - Konstantinos Tsanakas; Giannis Saitis; Niki Evelpidou; Efthimios Karymbalis; Anna Karkani (Quaternary, 2022)
Combined with eustatic sea-level changes, uplifted Quaternary marine terraces provide insight into the tectonics of coastal areas. Cephalonia Island lies 35 km off the western coast of mainland Greece and 15 km northeast of the Hellenic subduction zone. Late Pleistocene eustatic sea-level oscillations and the long-term tectonic movements are imprinted on the landscape of the southern part of the island, in the form of seven uplifted marine terraces. In the present study we aim to identify and map in detail these terraces, applying Digital Elevation Model analysis, utilizing Geographic Information Systems techniques and extensive fieldwork. The GIS-based analysis combined with field geomorphological observations revealed a sequence of seven marine terraces at the southern part of the main island ranging in elevation between 4 m and 176 m asl. Microscope, petrological and microgeomorphological analyses on two caprock samples suggest strong marine influence during the deposition of the sediments covering the marine terraces. The age of the formation of the 32 m marine terrace was assigned to the MIS 3e, based on OSL dating of a caprock sample, and an average uplift rate of 1.4 ± 0.35 mm a−1 was calculated for the last 61 ± 5.5 ka. Assuming a uniform uplift rate for the Late Pleistocene allowed us to correlate the marine terrace with the sea-level highstands and constrain their ages.